Motivación escolar y rendimiento académico en alumnos del cuarto año de secundaria de una institución educativa estatal de Ventanilla - Barrientos Chuqui, Leonor Lidia (2011)
This study tries to establish the relationship between the variables school motivation and academic performance in fourth-grade students at the secondary level, taking as an evaluation tool of school motivation questionnaire adapted for this population. The sample consisted of two hundred students of both sexes of public school “Villa Los Reyes.” The psychometric analysis of the evidence has required an adjustment, which became the validity and reliability required for use as measuring tools in this research. The methodology used was of a substantive, descriptive, correlational design. The contrast of hypotheses allowed to validate the hypotheses, and found a significant correlation between school motivation and academic performance.